Human Resource Development Strategy in Improving Employee Performance at Tanjungpinang Youth and Sports Service - Azahra Atikah; Azylla Febryanti; Febyolla Valentina Saputri; Satriadi Satriadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Human resource (HR) capability is the main key to the success of organizational development. The Youth and Sports Agency (Dispora) of Tanjungpinang City has a strategic role in youth and sports development, but HR development in improving employee performance is still not optimal. This study aims to analyze HR development strategies in improving employee performance at Dispora Tanjungpinang. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Informants consisted of structural officials, implementing staff, and parties directly involved in youth and sports programs. Data analysis was carried out using an interactive model that included data reduction, data presentation, and concluding, and its validity was tested through triangulation. The results of the study showed that the HR development strategy implemented by Dispora included motivation through training linked to careers and financial incentives, an integrated performance evaluation system, measuring the impact of training through systems and questionnaires, and cross-sector collaboration. Dispora also designed HR development that was in line with the Mayor's vision and mission, even though it still faced the challenge of budget constraints. These strategies are considered effective in encouraging improved employee performance and professionalism.